Sex Differences in Clinical and Functional Outcomes among Patients Treated in an Early Intervention Service for Psychotic Disorders: An Observational Study. (October 2019) - Dama, Manish; Veru, Franz; Schmitz, Norbert; Shah, Jai; Iyer, Srividya; Joober, Ridha; Malla, Ashok
Objective: It has been shown that men with a longstanding psychotic disorder have worse clinical and functional outcomes than women. Our objectives were to examine whether these sex differences are also present among patients treated in an early intervention service (EIS) for psychosis and to determine if these differences are related to risk factors other than sex. Method: Patients ( N = 569) were assessed for demographic/clinical characteristics at entry and for symptoms/functioning over 2 years of treatment. Clinical outcomes included remission of positive, negative, and total symptoms. Functional outcomes included good functioning and functional remission. Logistic regression models examined the relationship between sex and outcomes after 1 and 2 years of treatment while controlling for the influence of other risk factors. Results: Men reported to be less educated and have a longer duration of untreated psychosis, poorer childhood and early adolescent premorbid functioning, higher rates of substance abuse/dependence disorders, greater severity of baseline negative symptoms, and poorer baseline social/occupational functioning than women. Women were more likely to achieve symptom remission than men after 2 years of treatment (negative odds ratio [OR], 1.69; 95% confidence interval [CI], 1.02 to 2.78; total OR, 1.79; 95% CI, 1.08 to 2.98). Women were also more likely than men to exhibit good functioning (OR, 1.61; 95% CI, 1.04 to 2.49) after 1 but not after 2 years of treatment. These results did not persist after controlling for other risk factors that could confound these associations (i.e., childhood premorbid functioning and age at onset of psychosis). Conclusions: Sex differences seen in outcomes among patients treated in an EIS for psychosis may be largely influenced by the disparity of other risk factors that exist between the 2 sexes.